'Not my task': Role perceptions in a green transition among shop stewards in the Norwegian petroleum industry. (September 2022) - Houeland, Camilla; Jordhus-Lier, David
In the petroleum-dependent Norwegian economy, climate change politics challenge the powerful petroleum industry, and Norwegian shop stewards in that industry find themselves in cross-pressures of representation and responsibility. In this article, we investigate what role trade unionists in the oil sector play and can play, in a green and just transition. We analyse data from six focus group interviews with shop stewards in the petroleum industry. By engaging with theories of roles and role perceptions in light of labour agency, we fill a theoretical gap in the conceptualization of workers' collective agency. Respondents describe themselves as active part of a green transition in their capacity as workers, but the role of shop stewards neither seem to offer tools nor a mandate for representing environmental concerns: Climate change is not their task. Shop stewards respond to externally ascribed role expectations by insisting that primary agency resides with politicians, companies and consumers–and union leaders. Their reactive and ambiguous role interpretation can prove risky, as the employment outlook in the industry is changing radically and rapidly. Last, we find that there are both a need and potential for re-scripting shop stewards' role that is active and relevant in the green transition.